What to do in therapy in the face of HIV drug resistance? - Wainberg, Mark (Henry Stewart Talks, 2007)
Drug resistance in HIV disease can occur for each drug used in therapy, Drug resistant forms of HIV can be sexually transmitted, Drug resistance can be selected by antiviral drugs, HIV mutations can interact with one another to affect phenotype, Newer drugs in each class can work against resistant forms of HIV, New drug classes continue to be developed
Archived at 2018/10/28